The Conflict Between General Equilibrium and the Marshallian Cross - Ismail Saglam; Asad Zaman (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
There is a conflict in the mechanism for price determination used in a Marshallian partial equilibrium supply and demand framework and the Walrasian general equilibrium framework. It is generally thought that partial equilibrium is a simplified approximation to the complexities of the general model. The goal of this paper is to show that there is a strong conflict between the two models - intuitions and heuristics suggested by partial equilibrium are contradicted by extensions to the general equilibrium case. We review the literature on the conflict and also provide a very simple model where partial equilibrium analysis fails completely. Several intuitively plausible remedies fail to restore partial equilibrium results. We show that Marshallian analysis can be made to work only under rather stringent conditions requiring joint production with low fixed costs and decreasing returns resulting in identical production proportions by all producers.
Keywords: 330; Partielles Gleichgewicht; Nachfragetheorie des Haushalts; Allgemeines Gleichgewicht; Theorie